Cell wall distracting anti-Methicillin-resistant Staphylococcus aureus compound PVI331 from a marine sponge associated Streptomyces - Iniyan, Appadurai Muthamil; Mary, Thankaraj Rajam Jabila; Joseph, Francis-Joseph Rosemary Sharmila; Kannan, Rajaretinam Rajesh; Vincent, Samuel Gnana Prakash (Journal of Applied Biomedicine, 2016)
Isolation of unexplored frontier molecules are needed to treat multidrug resistant pathogens especially Methicillin resistant Staphylococcus aureus (MRSA). A marine sponge endosymbiotic Streptomyces albus ICN33 produces an anti-MRSA metabolite is reported. The crude extract exhibited anti-MRSA activity and the active principle was isolated through fermentation and chromatographic techniques. A compound PVI331 with a molecular mass of 506 Da have been determined by high resolution mass spectrometry. LC–MS based dereplication analysis had revealed that the detected compound PVI331 as unknown. The antibacterial assay of the compound PVI331 showed remarkable antagonistic activity against MRSA and Escherichia coli. Minimum inhibitory concentrations were found to be 1 μg/ml against MRSA. Sub-inhibitory concentration of the compound PVI331 reduced the biofilm formation of Staphylococcus aureus ATCC25923 and increased the cell surface hydrophobicity index. Scanning electron microscopic observation of the sub-inhibitory concentration exposure revealed a wrinkled membrane surface and slight cellular damage shows the cell wall distracting property of the compound. Zebrafish embryo based toxicity assays exhibited 48 ± 2 μg/ml of LC50 value and 30 μg/ml of compound as maximal non-lethal concentration which had demonstrated the positive relationship in safety index. This study highlighted the anti-MRSA property of Streptomyces albus ICN33 from a marine sponge.
Keywords: embryo nesavčí; dánio pruhované; Porifera; Zebrafish; Embryo, Nonmammalian; vztah mezi dávkou a účinkem léčiva; biofilmy; Dose-Response Relationship, Drug; antibakteriální látky; Anti-Bacterial Agents; Biofilms; Streptomyces; Methicillin-Resistant Staphylococcus aureus; methicilin rezistentní Staphylococcus aureus